Renewable energy transition in Europe in the last two decades - Mempel-Śnieżyk, Anna; Hlaváček, Petr; Hajduga, Piotr (Transformacja energetyki odnawialnej w Europie w ciągu ostatnich dwóch dekad, 2024)
Aim: The article aims to explore the evolution of the share of renewable energy in selected European countries over the period from 2005 to 2022 by examining countries with varying levels of renewable energy penetration and highlight regional disparities in renewable energy growth. Methods: This study uses quantitative analysis of Eurostat’s energy data to examine the share of renew-able energy in total final consumption across European countries in 2005, 2012, and 2022. Descriptive statistics, comparisons, and trend analysis are supported by visualizations, including maps, bar, and line charts, to illustrate changes over time. Results: The results reveal substantial progress in renewable energy adoption across Europe between 2005 and 2022, with notable variability in growth rates between countries, underscoring both the successes and the challenges faced in achieving energy transition. Implications and recommendations: The findings highlight the need for targeted policies and support mechanisms to assist countries with slower renewable energy adoption, particularly in addressing economic constraints and structural barriers that hinder progress. Originality/value: This study provides a comprehensive analysis of renewable energy growth across Europe from 2005 to 2022, offering unique insights into regional disparities and the factors contrib-uting to the varying pace of renewable energy adoption.
Biblioteka Regionalisty = Regional Journal, 2024, Nr 24, s. 21-30
Keywords: Dolny Śląsk